BEHAVIOR OF FORCE/RESISTANCE OF SUPERIOR MEMBERS AND OF THE FAT PERCENTAGE IN SCHOLARS OF HIGH SOCIOECONOMIC LEVEL (Fiep Bulletin - online, 2015)
The purpose of this study was to analyze the force/resistance of superior members (FMS) and the fat percentage (%G) of scholars, from 7 to 11 years of age, from high socioeconomic level of Florianópolis, SC. The sample was constituted of 285 scholars of the fundamental teaching (130 male (45,6%) and 155 female (54,4%) of the public and private teaching system). In the constitution of the sample, the schools and the scholars were selected by convenience. The socioeconomic level was identified through the questionnaire of socioeconomic classification published by the National Association of Company of Research - ANEP (1997). In the collection of data the anthropometric measure was used (thickness of skinfolds), and the test of the modified bar, proposed by the FITNESSGRAM battery, of Cooper Institute for Aerobics Research (1999). The analysis of the data was accomplished through the descriptive statistics, variance analysis ANOVA One-Way, with the use of the test post hoc of Scheffé (p
Keywords: fat percentage; force of superior members; scholars of high socioeconomic level.